Aggressive periodontitis: case definition and diagnostic criteria. (June 2014) - Albandar, Jasim M.
Abstract: Aggressive periodontitis is a destructive disease characterized by the following: the involvement of multiple teeth with a distinctive pattern of periodontal tissue loss; a high rate of disease progression; an early age of onset; and the absence of systemic diseases. In some patients periodontal tissue loss may commence before puberty, whereas in most patients the age of onset is during or somewhat after the circumpubertal period. Besides infection with specific microorganisms, a host predisposition seems to play a key role in the pathogenesis of aggressive periodontitis, as evidenced by the familial aggregation of the disease. In this article we review the historical background of the diagnostic criteria of aggressive periodontitis, present a contemporary case definition and describe the clinical parameters of the disease. At present, the diagnosis of aggressive periodontitis is achieved using case history, clinical examination and radiographic evaluation. The data gathered using these methods are prone to relatively high measurement errors. Besides, this diagnostic approach measures past disease history and may not reliably measure existing disease activity or accurately predict future tissue loss. A diagnosis is often made years after the onset of the disease, partly because current assessment methods detect established disease more readily and reliably than they detect incipient or initial lesions where the tissue loss is minimal and usually below the detection threshold of present examination methods. Future advancements in understanding the pathogenesis of this disease may contribute to an earlier diagnosis. Insofar, future case definitions may involve the identification of key etiologic and risk factors, combined with high‐precision methodologies that enable the early detection of initial lesions. This may significantly enhance the predictive value of these tests and detect cases of aggressive periodontitis before significant tissue loss develops.